A Secure Multimedia Data Sharing Scheme for Wireless Network. (18th October 2018) - Fang, Liming; Liu, Liang; Xia, Jinyue; Sun, Maosheng
Abstract : A large number of wireless devices like WiFi cameras and 4G robots have been deployed in the rapidly growing wireless network such as Internet of Things. All of the devices (sensors) are collecting and analyzing multimedia data all the time while they are actively working, and it is also required to share data among these the sensors. Typically, the wireless data is transmitted through the network gateway or the cloud platforms. In such a wireless environment, if there is no appropriate protection to the data, it is easy to cause potential data leakage. In reality, the owner of the sensor might only want to share the multimedia data stored in the sensor with a trusted third party (e.g., a family member or a coworker) through an internet gateway or the cloud platform. Ideally, the gateway or the cloud platform in the wireless network should transform one user's encrypted data (wireless multimedia data) directly into another ciphertext under a set of new users (e.g., a trusted third party) without accessing the user's plaintext data. In this work, a new secure notion called fuzzy-conditional proxy broadcast re-encryption (FC-PBRE) is presented to address the concern. In a FC-PBRE scheme, the proxy (the gateway or cloud server) uses a broadcast re-encryption key to re-encrypt the encrypted wireless multimedia data which can be decrypted by a set of delegatees if and only if the broadcast key's conditional set W is close to the conditional set W ′ of the ciphertext. With the FC-PBRE scheme, the wireless multimedia data is not disclosed and cannot be learnt by the proxy (the gateway or cloud server). In this paper, we first present the definition of security against chosen-ciphertext attacks for FC-PBRE. Second, we propose an efficient fuzzy-conditional proxy broadcast re-encryption scheme. Third, we prove that our FC-PBRE scheme is CCA-secure in the random oracle model based on the Decisional nBDHE assumption.